Laminarin enhances the activity of natural killer cells in immunosuppressed mice - Xiaobao Zhu; Renzhong Zhu; Zhiyuan Jian; Hong Yu (Central European Journal of Immunology, 2020)
The aim of the study was to investigate the effects of laminarin on natural killer (NK) cell cytotoxicity of immunosuppressive mice and its mechanism. Cyclophosphamide (cy) was used to make an immunosuppressive model of mice. The mice of two groups were given interventions by gavage with laminarin 500 mg/kg and 1000 mg/kg every day for 10 days. MACS was adopted to isolate spleen NK cells, and cytotoxicity of NK cells and IL-12, IFN- level in serum were detected in vivo . Cytotoxicity of NK92-MI cells, activating receptors (NKp30, NKp44, NKp46 and NKG2D) and perforin and granzyme B expression were detected in vitro . Compared to the normal control group, the cytotoxicity of NK cells, IL-12 and IFN- level in serum in the cy model group were all reduced significantly (p < 0.01). Compared to the cy model group, laminarin increased the cytotoxicity of NK cells, IL-12 and IFN- levels in serum significantly (p < 0.05). In vitro, laminarin increased the cytotoxicity, NKp30 and NKG2D, perforin and granzyme B expressions of NK92-MI cells (p < 0.01). This research showed that laminarin can promote NK cell cytotoxicity in immunosuppressive mice by increasing the levels of IL-12 and IFN- in serum and expressions of NKp30 and NKG2D, perforin and granzyme B.